How will the digital euro work? A preliminary analysis of design, structures and challenges - Volker Brühl (Goethe University Frankfurt, Center for Financial Studies (CFS), 2025)
The digital euro project will reach an important milestone this year when the preparation phase ends and the governing council of the ECB will decide whether to enter the next phase before the launch phase. This article provides an overview on how a digital euro is intended to work. An examination of the prospective design features and architecture of the digital euro reveals the complexity of the project and the challenges associated with integrating the digital euro into the existing payment landscape.
Keywords: E42; E51; G21; 330; Euro; Virtuelle Währung